WATERMARKING DENGAN QRCODE DIGUNAKAN UNTUK VERIFIKASI PADA WEBSITE - Nuryadi, Hepi (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2017)
With the development of digital technology and the internet today more and more works Digital image is duplicated. However this will be detrimental to the original owner or owner of the digital image. Therefore, a means of providing copyright protection or ownership of the digital image works is required. One way is done by watermarking technique, which is a method to insert a watermark into a digital image. And for verification of the Watermark the insertion on the watermak uses QR Code (Quick Response Code) in order to prove the ownership of a digital image